PERAN PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA DI PERPUSTAKAAN SMP PGRI 1 DENPASAR - Sanjaya, Kadek Yudhita; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT The Advance of library on reading interest increased in SMP PGRI 1 Denpasar’s Library This research is descriptive research in which use qualitative approach. The explicit of Library advance on reading proclivity increasing material is improve in this research, to meet the objective there 5 informant in Library of SMP PGRI 1 Denpasar To analyze the data are uses observation and interview technique. In this research, the tabulation data can be analyze by reduction, offering data, and conclusion from the data, to cover on offering data it’s use short explaination or narrative text. The library of SMP PGRI 1 Denpasar take important role on reading proclivity, these facts improve on excessively students visit and great quantities on book borrowed every day in The Library of SMP PGRI 1 Denpasar. The library tool and infrastructure is important things to be proclivity on reading in the library of SMP PGRI 1 Denpasar and there is no research yet on reading proclivity in The Library of SMP PGRI 1 Denpasar. Keywords: An advance of Library, Reading interest.